Critical realist exploration of long-term outcomes, impacts and skill development from an Australian Rural Research Capacity Building Programme: a qualitative study. Issue 12 (9th December 2022) - Schmidt, David; Duncanson, Kerith; Webster, Emma; Saurman, Emily; Lyle, David
Abstract : Objectives: Research capacity building programmes usually only examine short-term outcomes, following up participants after 1 or 2 years. Capacity building in health research requires a long-term view to understand the influence and impact of capacity building endeavours. This study examined long-term outcomes for individuals regarding the maintenance and use of research skills and the conduct of real-world research in a rural area. We also explored the changes individuals had seen in their career, work team or organisation as a result of this training. Design: A qualitative study underpinned by critical realism and based on interviews and focus groups with graduates of the Rural Research Capacity Building Programme (RRCBP), a researcher development programme that has been delivered since 2006. Setting: Rural and remote areas of New South Wales, Australia. Participants: 22 graduates of the RRCBP from the 2006 to 2015 cohorts (20 female, 2 male). All were experienced rural-based health workers at the time of training. Results: Focus groups and interviews yielded three themes about capacity building outcomes: (1) developed research capable individuals; (2) embedded research capability into teams and (3) real-world research that makes a difference within an organisation. Conclusions: Research training improved graduates' skill, experience, confidence and employability. Research capable individuals enabled others, enhancing team research capacity and raising the profile of research within their organisation. Training in research, alongside tangible organisational support for research activity, creates real-world impacts for policy and clinical practice. Providing ongoing opportunities for researchers to undertake research would enhance return on investment and assist with retention of experienced staff.